146P The dynamics between neo-adjuvant treatment and immune responses in human breast cancer. (15th December 2019) - Thomas, N; Garaud, S; De Wind, A; Pabois, A; De Silva, P; Craciun, L; Boisson, A; Naveaux, C; Duvillier, H; Larsimont, D; Awada, A; Willard-Gallo, K
Abstract: Background: Recent work has shown that immune activity in breast cancer (BC) plays a role in treatment responses and long-term outcomes. TIL scoring is now implemented as a prognostic marker in clinical practice. Studies show that high tumor infiltrating lymphocytes (TIL) are more often detected in triple negative and HER2 positive subtypes. TIL contain a heterogeneous population of immune cells dominated by T cells but also consist of many others. Neoadjuvant therapy (NAT) is increasingly administered in patients with locally advanced BC, allowing a resection of the tumor and to evaluate the in vivo response. While cytotoxic agents such as Anthracyclines elicit immunogenic cell death, the impact of NAT on TIL has only been sporadically studied. Methods: A detailed assessment of the tumor microenvironment (TME) includes evaluation of TIL density, composition and functionally. Following NAT, lymphocyte subpopulations were quantified using flow cytometry(FACS) and these data were compared to untreated BC patients. Tumor tissue supernatants were stored for assessment of immunoglobulins (Ig). The FFPE blocks from matched biopsies and surgical tissues were stained with HE, chromogenic IHC and multiplex IHC. The stromal and intratumoral TIL were scored by two experienced pathologists. Results: Our preliminary data correlate better responses with highly infiltrated biopsies, consistent with published work. Overall, the trend following NAT is for a decrease in TIL density, but with great inter-patient variation. FACS analysis of immunophenotypes shows a shift from CD4 to CD8 T cells and an increase in memory B cells after NAT. An assay for Ig subtypes detected decreases in IgG1/IgM and increases in IgG2/IgA. Multiplex IHC analysis of the TME in a patient with residual cancer detected active immune responses surrounding the remaining tumor that were characterized by CD8 TIL attached to the malignant cells, suggesting their recognition and killing. Conclusion: NAT provokes changes in immune activities at the tumor site in early BC, with some of these alterations apparently linked to specific treatments. Our ongoing efforts are designed to provide detailed insight into the alterations associated with different NAT modalities and define prognostic biomarkers. Legal entity responsible for the study: The authors. Funding: FRNS, Télévie, Les Amis de l'Institut Bordet, Lambeau Marteau. Disclosure: A. Pabois: Full / Part-time employment: Iteos therapeutics. All other authors have declared no conflicts of interest.